Academic and Family Balance: A Comparative Study of Married Postgraduate Students in Islamic Higher Education in Indonesia and Brunei Darussalam - Ahmad Muthohar; Raharjo Raharjo; Anis Malik Thoha; Nasikhin Nasikhin (Nazhruna: Jurnal Pendidikan Islam, 2025)
This study aims to compare the experiences of married students in maintaining a balance between academic and family life in Indonesia and Brunei Darussalam. This study used a comparative qualitative research method with a phenomenological approach. Data were collected through in-depth interviews, participatory observation, and document analysis. Data analysis was conducted using the Miles and Huberman model. This study's findings show significant differences and similarities in the motives for continuing postgraduate studies between married students in Brunei and Indonesia. Students in Brunei tend to be driven by internal motives such as self-development and personal satisfaction, with government support and scholarship programs playing an important role in their motivation. In contrast, students in Indonesia focus more on career achievement and professional incentives such as salary increases and scholarships, as well as personal satisfaction from academic achievement. Significant differences also emerged in academic achievement, domestic relationships, and career progression. The financial support provided by the Brunei government allows students to focus more on their studies and maintain a balanced home life. In contrast, students in Indonesia often have to bear the financial burden alone, which results in stress and delays in graduation. Financial pressures in Indonesia also affect the stability of domestic relationships and long-term career planning, with students focusing more on short-term employment than future planning. These findings support the Work-Family Balance theory, providing recommendations that institutional religion and cultural norms should develop adaptive policies so that students can face dual demands in a balanced manner.